International experience in organizing international air service - Стрибко, Тетяна Іванівна; Стрибко, Т. І.; Стрыбко, Татьяна Ивановна; Strybko, Tetiana I.; Шай, Роман Ярославович; Шай, Р. Я.; Shai, Roman Ya.; Заболотна, Наталія Ярославівна; Заболотна, Н. Я.; Заболотная, Наталия Ярославовна; Zabolotna, Nataliya Ya. (INCAS, 2020)
The purpose of the article is to study the effectiveness of regulation and practice of organizing international air transport service, analysis of tendencies and prospects for the development of a regulatory framework on a global scale. The basic elements and acts of international legal regulation of air transportation at the international level are identified. The relevance and the need to include Ukraine in the international legal framework in the air service industry were proved. The levels of state regulation of air transport are outlined. A comparative analysis of the regulatory support of the air industry in Ukraine and in other countries is performed. The level of Ukraine’s inclusion in the international legal scope of regulation of air transport space and the main achievements in this process are estimated. The applied value of the work is to develop priority areas for the implementation of Ukrainian legislation to international air service standards, an algorithm of actions for signing an agreement on collaborative airspace.

Метою статті є вивчення ефективності регулювання та практики організації міжнародного обслуговування повітряного транспорту, аналіз тенденцій та перспектив розвитку нормативно-правової бази в глобальному масштабі. Визначено основні елементи та акти міжнародно-правового регулювання повітряних перевезень на міжнародному рівні. Доведено актуальність та необхідність включення України до міжнародно-правової бази в галузі авіаперевезень. Окреслено рівні державного регулювання повітряного транспорту. Проведено порівняльний аналіз регуляторного забезпечення повітряної галузі в Україні та інших країнах. Оцінено рівень включення України до міжнародно-правової сфери регулювання простору повітряного транспорту та основні досягнення у цьому процесі. Практична цінність роботи полягає у розробці пріоритетних напрямів імплементації законодавства України до міжнародних стандартів повітряного сполучення, алгоритму дій для підписання угоди про спільний повітряний простір.

Целью статьи является изучение эффективности регулирования и практики организации международного авиатранспортного обслуживания, анализ тенденций и перспектив развития нормативной базы в мировом масштабе. Выявлены основные элементы и акты международно-правового регулирования авиаперевозок на международном уровне. Доказана актуальность и необходимость включения Украины в международно-правовую базу в сфере авиаперевозок. Обозначены уровни государственного регулирования воздушного транспорта. Проведен сравнительный анализ нормативного обеспечения авиационной отрасли Украины и других стран. Оценивается степень включения Украины в международно-правовую сферу регулирования воздушного транспорта и основные достижения в этом процессе. Прикладная ценность работы заключается в разработке приоритетных направлений по имплементации украинского законодательства в международные стандарты воздушного сообщения, алгоритма действий для подписания соглашения о совместном воздушном пространстве.
Shai R. Y. International experience in organizing international air service / R. Y. Shai, T. I. Strybko, N. Y. Zabolotna // INCAS Bulletin. – V. 12. – INCAS, 2020. – P. 169-179.
Keywords: international aviation; air transportation; international legal regulation; implementation of provisions; міжнародна авіація; повітряні перевезення; міжнародно-правове регулювання; імплементація положень; международная авиация; авиаперевозки; международно-правовое регулирование; имплементация положений; Research Subject Categories::LAW/JURISPRUDENCE